Identification of novel biomarkers in plasma for prediction of treatment response in patients with heart failure. (26th February 2015) - Cao, Thong Huy; Quinn, Paulene A; Sandhu, Jatinderpal K; Voors, Adriaan A; Lang, Chim C; Parry, Helen M; Mohan, Mohapradeep; Jones, Donald J L; Ng, Leong Loke
Abstract: Background: Heart failure is a complex clinical syndrome that occurs at the end stage of heart disease. Despite advances in therapy for heart failure, improvement of clinical outcomes remains a challenge for physicians. The identification of treatment response early in the course of disease would be useful to improve management of these patients. The aim of this study was to identify novel biomarkers in plasma that could predict treatment response in patients with heart failure. Methods: Patients with heart failure who met inclusion and exclusion criteria according to the guidelines of the European Society of Cardiology were recruited. Uptitration of angiotensin-converting enzyme inhibitors and β blockers was performed over 6 months. Patients were followed up for clinical events within the next 24 months. Plasma proteins in patients who responded to standard treatment (responders) were compared with patients who died or were re-admitted for heart failure (non-responders). Plasma samples were depleted of 14 high abundance proteins with a multiple affinity removal system column (MARS). Then plasma samples were analysed on two-dimensional liquid chromatography coupled to a tandem mass spectrometry (2D LC-ESI-MS/MS) in high definition mode (HDMS E ) to identify and quantify the different expression of proteins in plasma. Finally, ELISA was used to verify candidate biomarkers. Findings: Participants were 100 patients with heart failure matched for sex and age (50 responders [25 women], 50 non-responders [25 women], mean age 76·6 years [SD 8·1]). Of the non-responders, 18 died and 32 were re-admitted to hospital. 2D LC-ESI-MS/MS showed that the expression of neurotrimin (NTM) was highly upregulated, by 26·5 times (p<0·0001), in the responder group compared with the non-responder group. ELISA in the verification phase showed that the concentrations of NTM in plasma were significantly higher in the responders and lower in the non-responders (mean 4·73 log10 relative light units [SD 0·07] vs 4·70 [0·08], p=0·036). When ANOVA with Bonferroni post-hoc comparisons was used in three outcome subgroups (responders, patients re-admitted to hospital, and deaths), NTM concentrations were significantly different between death and the other groups (higher in responder vs death group, p<0·0001; higher in re-admission vs death group, p=0·001). Interpretation: Our findings suggest that NTM as a novel biomarker in heart failure will not only add information to understand the pathophysiological mechanisms of heart failure better, but also might provide a more accurate prediction of treatment response to guide medical therapy. In addition, a novel therapeutic target could be identified for design of drugs to improve outcomes. Futher work is required in larger populations to confirm this biomarker. Funding: European Union's Seventh Framework Programme (BIOSTAT-CHF), John and Lucille van Geest Foundation.